The Communicative Construction of Reality and Sequential Analysis. A personal reminiscence - Luckmann, Thomas (Qualitative Sociology Review, 2013)
This paper presents a historical view of the emergence of what is known as the communicative paradigm. Through a personal reminiscence of his long career, Thomas Luckmann entangles the main sources of what was a radical shift of the role of language and communication in the humanities and social sciences. In doing so, Luckmann shows that the epistemological and ontological assumptions on which the contemporary study of social interaction and communicative processes rely were practically non-existent half a century ago. While sociology and linguistics seemed to exist in separate universes during Luckmann’s student days, a dialogical approach to language and social life eventually appeared – for example, in ethnomethodology, conversational analysis and French structuralism – and laid the foundation to the (today taken for granted) idea that social realities are the result of human activities. Human social reality and the worldview that motivates and guides interaction are mainly constructed in communicative processes. If social reality is constructed in communicative interaction our most reliable knowledge of that reality comes from reconstructions of these processes. Such reconstructions have been greatly facilitated by technological innovation, such as tape- and video-recorder, which, alongside theoretical advancements, may explain the timing of the communicative turn. Finally, this paper marks the benefits of sequential analysis in enabling us to trace step-by-step the processes by which social reality is constructed and reconstructed.